Optimization of Complete Blood Count Results with Variations in Specimen Handling and Whole Blood Secondary Homogenization Techniques - Aliviameita, Andika; Puspitasari, Puspitasari; Primastuti, Yuridistya Putri; Batis, Afifah (Poltekkes Kemenkes Tanjung Karang, 2024)
Specimen homogenization and the addition of anticoagulants are pre-analytical steps that influence the accuracy of the test results. Complete blood count (CBC) is a screening test that supports disease diagnosis and aids in determining the appropriate therapy for patients. Inadequate specimens are inappropriate for subsequent testing, as they can lead to inaccurate results in the CBC examination. This study aims to determine the optimization of complete blood count results with variations in specimen handling and secondary homogenization techniques for whole blood. The type of research used is quantitative analysis using laboratory experimental methods. The study was conducted in May 2024 in the Clinical Pathology Laboratory of the Diploma-4 Medical Laboratory Technology Study Program, Faculty of Health Sciences, Muhammadiyah University of Sidoarjo, using 48 blood samples. The results of the MANOVA test indicate that the type of anticoagulant has a significant effect on the erythrocyte count (p=0.041) but does not have a significant impact on the leukocyte count (p=0.844) and platelet count (p=0.920). Meanwhile, the homogenization technique does not significantly affect the erythrocyte count (p=0.959), leukocyte count (p=0.991), or platelet count (p=0.867). This study concludes that the secondary homogenization technique has no significant effect. In contrast, the type of anticoagulant significantly impacts the results of the Complete Blood Count (CBC) test. This research suggests collecting whole blood specimens using Ethylene Diamine Tetra Acetate (EDTA) vacutainers as the anticoagulant and applying a secondary homogenization technique before performing the CBC analysis.